Texas Almanac 2014-2015 - Alvarez, Elizabeth Cruce (Book collections on Project MUSE., 2014)
FEATURES OF THE TEXAS ALMANAC 2014-2015 Sketches of eight historic ranches of Texas by Texana writer Mike Cox. Article on the Texas art and artists by Houston businessman and art collector J.P. Bryan, who has amassed the world's largest Texana collection. Coverage of the 2012 elections, redistricting, and the 2012 Texas Olympic medalists. An update on Major League Baseball in Texas. Lists of sports champions - high school, college, and professional. MAJOR SECTIONS UPDATED FOR EACH EDITION The Environment, including geology,